Você está na página 1de 30

 

R n

 

x n (x n ) [x n ] = sup{m Z|m x n } {x n } x n [x n ] 0 ≤ {x n } < 1 x n {x n } [0, 1)

(x n ) a, b 0

a < b < 1

lim

N →∞

#{x n ; {x n } ∈ [a, b] : 0 n < N }

N

= b a

(x n ) [0, 1) x [0, 1) > 0 I (x n ) = I = (x , x + ) S N = 0 N N

I

I

lim N S N = 0 S

I

N

= #{x n ;{x n }∈I:0n<N }

N

() N α

α h

= 0

e 2πihα = 1

N N

e 2πihnα =

e

(2πihα)n

n=1 n=1

1

N

|

N

n=1

(e 2πihNα 1)e 2πihα

(e 2πihα 1)

e 2πihnα | | (e 2πihNα 1)e 2πihα

N(e 2πihα 1)

e 2πihNα 1

| | N(e 2πihα 1) |

|e 2πihNα |+|1|

2

N|(e 2πihα 1)| N|(e 2πihα 1)|

(e 2πihα 1) N

lim

N →∞

1

N

N

n=1

e 2πihnα = 0

h

= 0 α

x n x n

x n x 0

(x 0 , x 0 + ) ∩ {x n } =

lim

N →∞

#{x n [x 0 , x 0 + ] : 0 n < N}

N

n N

(0, 1]

= 0

= 2

>

0

x n k Z {0}

lim

N →∞

1

N

N

n=0

exp(2πkix n ) = 0

[1]

x n n=0 exp(2πkix n )

N

(x n ) k k

(x n )

c

= 0 (cx n )

(x n )

lim

N →∞

1

N

N

n=1

e 2πihx n = 0

h

h Z, h = 0

= 0 ch h

lim

N →∞

1

N

N

n=1

e 2πich x n =

lim

N →∞

1

N

N

n=1

e 2πih (cx n ) = 0

= 0

(cx n )

x = (x n ) n=0 Γ(x) = γ([0, )) R 2 C

γ(0) = (0, 0)

γ(n) = n1 exp(2πix k ) n = 1, 2,

k=0

γ(t) n t n + 1

n 2πu n

exp(2πix n ) = exp(2πi( x n +{x n })) = exp(2πi{x n }) γ(x n ) = γ({x n })

(n 2 π) Γ(n 2 π) 5000

“ π curlicue ” − Γ 5 0 0 0 ( n 2 π )

π curlicueΓ 5000 (n 2 π)

d(·, ·) A C > 0

DiamA = sup{d(x, y); x, y A}

Γ DiamΓ < DiamΓ = Γ() Γ(n)

(i) Γ

t

lim

t→∞

=

DiamΓ t Γ t Γ t

(ii) Γ

lim

0

AreaΓ

=

Γ = {y; x Γ, d(x, y) < }

Γ

(x n ) Γ(qx n ) q

x = (x n ) q

z n (q) =

n1

k=0

exp(2πiqx k )

Γ(qx) q Z + Γ(qx)

|z n (q)| ≤ DiamΓ n (qx)

lim

n→∞

DiamΓ n (qx)

n

= 0

()

n ( qx ) lim n →∞ Diam Γ n ( qx ) n = 0

()

lim n→∞

n

DiamΓ n (qx) =

lim n→∞

DiamΓ n (qx)

n

=

0

()

lim n→∞

|z n (q)|

n

=

0

(x n ) (x n ) q Z +

lim n→∞

|z n (q)|

n

=

0.

DiamΓ n (qx) 2 max

0k<n |z k (q)|.

n = k |z n (q)| |z k (q)|

lim n→∞

max 0k<n |z k (q)|

lim n→∞

n

DiamΓ n (qx)

=

n

= 0

0

a n b n

b 2n = 0

b n = (0, a 1 , 0, a 2 , 0,

)

b 2n+1 = a n

(b n ) S

1

(x5 ,x+

N

1

5 )

1

2 N N

(b n )

b pn+k = c k ,

b pn+p1 = a n

k = 0, 1, 2,

, p 2

 

2 p N c k R a n

p 1 (a n )

a n = b n

(b n ) = (0, 1/4, a 0 , 0, 1/4, a 1 ,

b 3n = 0

b 3n+1 =

1

4

b 3n+2 = a n

.)

, b 3 n = 0 b 3 n +1 = 1 4 b 3 n

Γ 120 () Γ 110 (b n )

(x n ) Γ(x n )

v(x n ) =

lim

N →∞

S N

N

S N =

N

n=0

exp(2πix n ).

R n

2 × 2 n × n

f(x) = T A (x) = A.x = Ax,

f = T A (x) : R n −→ R n A.x = Ax A = (a ij ) n×n x A n × 1 x R n x : R −→ R n

x = Ax

x R t R

x (t) = Ax(t)

x : R −→ R n x = Ax x(0) R n

A = (a ij ) n×n x 0 R n x = Ax, x(0) = x 0

[1]

x = Ax F (R, R n ) R R n

A, B M (n) M (n) n × n Q M (n) AQ = QB

A = QBQ 1

Q A B A B

Q A, B M (n) Q y = By x = Ax A = QBQ 1

y(t) y = By

Qy(t) x = Ax

Q t x(t) = Qy(t)

x (t) = Qy (t) = QBy(t) = AQy(t) = Ax(t)

Q

( t ) = Qy ( t ) = QBy ( t ) = AQy (

A M (n) Q, D M (n)

Q Q 1 AQ = D

=

diag(λ 1 ,

,

λ n )

1

i

n

Qe i = v i s i : R −→ R n

 

s i (t) = e λ i t Qe i = e λ i t v i t

R

x = Ax x(0) = v i

 

y

=

Dy

y(t)

=

(ι 1 e λ 1 t ,

,

ι n e λ n t )

 

=

ι j e λ j t e j y(0) = ι j e j

x = Ax

x(t) = Qy(t) = Q ι j e λ j t e j = ι j e λ j t Qe j = ι j e λ j t v j

x(0) = ι j v j = Q(ι 1 ,

y(t) = e λ i t e i y = Dy s i (t) = e λ i t v i x = Ax

, ι n ) y(0) = e i

t v i x = Ax , ι n ) y (0) = e i x

x = Ax

v R n A M (n) λ R

x(t) = e λt v, t R

x = Ax, x(0) = v

x(t) = e λt v

x = λe λt v = e λt λv = e λt Av = Ax(t)

= Ax, x (0) = v x ( t ) = e λ t v x

A M (n)

A n λ 1 , λ 2 ,

, R n

v 1 , v 2 ,

, v n

, λ n R

v n R v 1 , v 2 ,

λ n ∈ R v n ∈ R v 1 , v 2 , 2 ×

2 × 2 λ 1 λ 2 p A (λ) 2 × 2 A M (2)

= λ 2 A λ 0 1

λ 1 , λ 2 λ 1

λ 0 2

λ 1

λ 2

λ 0 = λ 1 = λ 2

λ 0 I A) = 2 A λ 0 1

λ 0 2

= λ 0 I

λ 0 I A) = 1 A λ 0 1

u λI A v = Au λ 0 u A λ 0

λ 0 2

λ 1 = a+ib λ 2 = aib a, b R b

a b

A

λ 1

= 0

A

a

b

[1]

w C n A M (n)

λa + ib b

= 0 w = u + iv

u =

2 1 (w + w¯)

e

v =

2i 1 (w w¯)

R n w = u + iv u, v R n

x(t) = e at [(cosbt)u (senbt)v] y(t) = e at [(senbt)u + (cosbt)v]

x = Ax x(0) = u e y(0) = v

[1]

x = Ax, x(0) = (k 1 , k 2 )

x = Ax A M (2) x = (x 1 , x 2 ) : R −→ R 2 x = Ax

{(x 1 (t), x 2 (t))|t R},

−∞ +

A M (2) a ± ib, b

= 0

Q M (2)

Q 1 AQ =

a

b

b a .

x = Ax

X(t) = e at Q

cosbt

senbt

senbt

cosbt

k

1

k 2

x(0) = Q(k 1 , k 2 ) Q = (u, v) (R 2 ) 2 = M (2) u, v R 2 w = u + iv Aw = (a + ib)w

x(t) =

e at [(cosbt)u (senbt)v]

y(t) = e at [(senbt)u + (cosbt)v]

x = Ax x(0) = u, y(0) = v R n

A

λ 1 = a + bi λ 2 = a bi b

= 0 a = 0

x =

a

b

a b x.

φ(t) = re at (cosb(t θ), senb(t θ)).

2 b π a = 0 (t)

(0, 0)

= (0, 0)

2 b π

t − θ ) , − senb ( t − θ )) . 2 b π

b < 0

x(t) = e ta x 0 x = ax x(t) = e tA x 0 x = Ax

e a =

j=0

1

j! a j

M (n) R n 2

||A|| = sup

|x|≤1 |Ax| = sup

|x|=1 |Ax|

A M (n) | . | R n

||AB|| ≤ ||A|| ||B||

A m A M (n)

||A m || ≤ ||A|| m , para cada m N

M (n) M (n)

A M (n)

e A = I + A +

1

1

2! A 2 + 3! A 3 +

+

1

j! A j =

j=0

1

j! A j .

M (n) || . || M (n)

j=0

1

|| j! A j || =

j=0

1

j! ||A j || ≤

j=0

1

j! ||A|| j = e ||A||

A

e tA emM (n) e t

e tA x 0 em R n

M (n)

x 0

d

dt e tA = Ae tA M(n),

d

dt e tA x 0 = Ae tA

[1]

R n t

R n

A M (n) x 0 R n

x(t) = e tA x 0 ,

t R,

x = Ax x(0) = x 0

[1]

x (t) =

x (t) = Ax(t) + b(t)

x 1 (t) x 2 (t)

x n (t)

; A =

a 11

a n1 ··· a nn

a 1n

···

; b(t) =

b 1 (t) b 2 (t)

b n (t)

x 1 (t) x 2 (t) 3.14 φ(t) = x 1 (t) x 2 (t) x = Ax(t)

x 1 (t) =

Ax 1 (t) +

b(t)

x 2 (t) = Ax 2 (t) +

b(t)

φ (t) = x 1 (t) x 2 (t) = Ax 1 (t) + b(t) Ax 2 (t) b(t)

= A(x 1 (t) x 2 (t)) = (t)

x c (t)

1 ( t ) − x 2 ( t )) = Aφ ( t ) x
 

x (t) = Ax(t),

φ(t)

 

x (t) =

Ax(t) + b.

X(t) 3.14

 
 

X(t) = x c (t) + φ(t).

x 1 (t) φ(t) 3.14 x(t)φ(t) X (t) = Ax(t)

X(t) φ(t) = c 1 x 1 (t) + ··· + c n x n (t)

x 1 (t), ··· , x n (t) n X (t) = Ax

c 1 x 1 (t) + ··· + c n x n (t) = x c (t)

3.21

X(t) = x c (t) + φ(t)

x 1 ( t ) + ··· + c n x n ( t ) =

x (t) = y(t) + 1 y (t) = x(t)

x(0) = 1, y(0) = 1

x c (t)

x (t) + y(t) = 0

y (t) x(t) = 0

c 2 = x c (t) = e At c

1

sen(t)

cos